New C-integrable and S-integrable systems of nonlinear partial differential equations. Issue 1 (2nd January 2017) - Calogero, Francesco
Abstract : A technique to identify new C-integrable and S-integrable systems of nonlinear partial differential equations is reported, with two representative examples displayed and tersely discussed.